Analisis Tindak Tutur Ilokusi pada Video Pembelajaran Teori Sosial & Kewarganegaraan dalam Channel Youtube GCED ISOLAedu - Nabila Dila Ardiyanti; Okti Nurdianti Akmah; Nia Mila Dina Setiani; Tyas Rahma Viani; Ika Apriliani; Asep Purwo Yudi Utomo; Tri Hutami Wardoyo; Fahrudin Eko Hardiyanto (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Currently, many teachers or lecturers are using educational videos as a learning tool for students. This research aims to identify and classify the types of illocutionary speech acts found in the educational videos on social theory and citizenship on the YouTube channel GCED ISOLAedu. This research employs two main approaches, namely theoretical and methodological. By utilizing a qualitative approach with a descriptive nature, the researcher will provide a detailed and in-depth depiction of the use of illocutionary acts in the video. The data collection process involves: (1) Gathering data through the technique of free observation and conversation involvement, as well as note-taking techniques, (2) Analyzing data using matching methods and distribution methods, and (3) Presenting the data analysis using both formal and informal methods. Based on the analysis conducted on seven educational videos on Social Theory & Citizenship 2024 on the YouTube channel GCED ISOLAedu. Researchers found 143 speech acts that contain illocution. The first illocutionary act is the representative speech act, with 118 data consisting of explanations and statements. Second, the commissive speech act has 2 data points involving offers and promises. Third, the expressive speech act includes 7 data points related to greetings and expressions of gratitude. Fourth, the directive speech act comprises 15 data points that involve asking, requesting, and inviting. Lastly, the declarative speech act contains 1 data points related to commands. The benefit of this research is to provide knowledge in the field of pragmatics, particularly regarding types of illocutionary acts, and to enable an understanding of these illocutionary acts without misunderstandings in receiving the information conveyed by the speaker.